3D Printing of Biocompatible Materials for Biomedical Applications - Cristóvão, Ana Filipa Mendes (2018)
In this work, we develop and test materials to be used in a 3D printed prosthesis, made according to each patients’ anatomy. These must be biocompatible, flexible and maintain airway permeability. Different polymeric materials based on PEGDA (polymer) and B2VT (photoinitia-tor) were studied, each with either PVA or SA and CaSO4. These hydrogels were crosslinked with UV light, one while printing by extrusion and the other after being deposited in casts. A systematic study was performed on the influence of laser power in in-situ reticulation and 3D printing of an SA and PEGDA/B2VT mixture, by testing their compression mechanical properties. This study was compared to samples with PVA, reticulated with UV light after 3D printing and the difference in terms of mechanical properties is enormous. First shows Young’s Modulus in the range of 4-6 MPa and the second in the range of 0.8-1 MPa. The results lead to the conclusion that higher percentages of PVA and B2VT increase the value of E and that the use of Alginate creates a material with a compression curve typical of foams.